Amphoteric 2-(sulfonylamino)benzaldehydes, secondary amines and isocyanides in the multicomponent synthesis of elusive N-alkyl-2, 3-diaminoindoles. Issue 45 (8th November 2017) - Giustiniano, Mariateresa; Pelliccia, Sveva; Sangaletti, Luca; Meneghetti, Fiorella; Amato, Jussara; Novellino, Ettore; Tron, Gian Cesare
Graphical abstract: Highlights: One pot synthesis of N -alkyl 2, 3-diaminoindoles. The sulphonamide group intercepts the nascent nitrilium ion. No transition metals required. Abstract: A novel interrupted Ugi reaction between ortho -sulfonylaminated aryl aldehydes, secondary amines, and isocyanides affords in good to high yields N -alkyl-2, 3-diaminoindoles, providing access to a so far unexplored area of the indole chemical space. With only one single chemical operation, this novel reaction affords a broad gamma of substituted 2, 3-diaminoindoles with five points of diversity. The success of this novel multicomponent transformation lies in presence of the amphoteric sulfonylamino group, which sequentially acts as a Brønsted acids and as a nucleophile the lack of need for additional catalysts and the high atom economy, with the loss of only one molecule of water, renders this approach a very effective one.